A new species of the genus Dorytomus Germar, 1817 (Coleoptera, Curculionidae) from Rovno amber - Legalov, Andrei A.; Nazarenko, Vitaliy Y.; Perkovsky, Evgeny E. (Zootaxa, 2021)
A new species, Dorytomus mikhailovi sp. n., from late Eocene Rovno amber is described and illustrated. The new species is similar to D. groehni Bukejs et Legalov, 2019 from Baltic amber but differs in the shorter rostrum, dorsum covered with denser decumbent hairs and erect to semierect scale-like setae, and smaller body sizes. It is distinguished from D. bukejsi Legalov, 2020 from Baltic amber by the densely punctate pronotum, longer rostrum and wide elytral interstriae. The new species differs from D. vlaskini Legalov et al., 2019 from Rovno amber by the elytral interstriae covered with decumbent hairs and erect to semierect scale-like setae, shorter rostrum and coarsely punctuate pronotum. It is the first named curculionid beetle from the Olevsk amber locality, and the eleventh amber species reported from the Zhitomyr region. The presence of seven species of Dorytomus suggests a rather high diversity of Salicaceae in the late Eocene amber forests of Europe. It corresponds well with other principal Holarctic species in European amber biotas.